Modern Approaches to Replacing the Method of Fixation in Gunshot Fractures of Long Bones - Бур’янов, О.А.; Ярмолюк, Ю.О.; Грицай, М.П.; Клапчук, Ю.В.; Лось, Д.В.; Омельченко, Т.М.; Колов, Г.Б.; Деркач, С.О. (TERRA ORTHOPAEDICA, 2023)
Modern Approaches to Replacing the Method of Fixation in Gunshot Fractures of Long Bones